Hubungan Pengetahuan dan Sikap dengan Perilaku Buang Air Besar Sembarangan (BABS) - Desi Mustika Wati; Yuanita Windusari; Nur Alam Fajar (LPPM Institut Pendidikan Nusantara Global, 2025)
Open defecation remains a significant public health problem in Indonesia despite various intervention programs implemented. Knowledge and attitudes are predisposing factors suspected to influence open defecation behavior, but there are still inconsistencies in research findings regarding the strength of their relationship with open defecation behavior. This study aims to analyze the relationship between knowledge and attitudes with open defecation behavior and identify which factor has the strongest relationship. This study used a qualitative approach with a literature review method on ten research articles published from 2021-2025. Literature search was conducted on academic databases using keywords